The effectiveness of virtual reality in people with osteoporosis or osteopenia: a systematic review and meta-analysis of randomized controlled trials - He, Shunxia; Dong, Shiqiu; Lin, Xiaoguang; Wang, Zhijie; Diao, Yuzi; Gao, Xiao (Frontiers in Physiology, 2025)
BackgroundOsteoporosis is a global bone disease, and drug therapy carries the risk of side effects, requiring exploration of safe and effective alternative therapies. Virtual reality (VR) has shown potential in rehabilitation medicine, but its efficacy in the management of osteoporosis and osteopenia has not been systematically evaluated.MethodUsing PubMed, Embase, the Cochrane Library, and Web of Science, we conducted a comprehensive database search to identify randomized controlled trials (RCTs) investigating the effects of VR on osteoporosis and bone loss. Trials published up to 30 March 2025 met our predefined inclusion and exclusion criteria. We extracted data, reviewed the literature. We assessed the methodological quality of the included trials and the certainty of the pooled evidence. Meta-analyses were performed using StataSE version 16.ResultsOur meta-analysis included 216 patients from 5 RCTs. All cases included in our study adopted the non-immersive VR intervention approach. Femoral neck bone mineral density (BMD) (standardized mean difference [SMD] = 0.77, 95% confidence interval [CI] = 0.35–1.19, P < 0.0001, I2 = 0%), balance (SMD = 2.58, 95% CI = 1.10–4.05, P = 0.001, I2 = 91.2%) and mobility (SMD = 1.63, 95% CI = 0.14–3.13, P = 0.032, I2 = 93.7%) were improved compared to the control group. However, lumbar BMD (SMD = 0.39, 95% CI: −0.02, 0.80, P = 0.062, I2 = 0%) and quality of life (QOL) (SMD = 2.50, 95% CI: −2.15, 7.16, P = 0.292, I2 = 97.4%) were not significantly improved compared to the control group. None of the included studies reported adverse events or safety data.ConclusionThis systematic evaluation provides valuable evidence for the management of osteoporosis and osteopenia through VR. However, given the overall low and very low level of evidence, the results need to be treated with caution. In the future, VR may be a potential treatment for osteoporosis and osteopenia.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251023178, PROSPERO, identifier CRD420251023178.